2014
DOI: 10.3382/ps.2013-03470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free-range days on a local chicken breed: Growth performance, carcass yield, meat quality, and lymphoid organ index

Abstract: An experiment was conducted to evaluate the effect of free-range days on growth performance, carcass yield, meat quality, and lymphoid organ index of a local chicken breed. In total, 1,000 one-day-old male Suqin yellow chickens were raised for 21 d. On d 21, 720 birds with similar BW (536 ± 36 g) were selected and randomly assigned to free-range treatment at 21, 28, 35, and 42 d of age (assigned to free-range treatment for 21, 14, 7, and 0 d, respectively). Each treatment was represented by 5 replicates (pens)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
(32 reference statements)
4
29
0
4
Order By: Relevance
“…Our observations revealed that thymus weight and the thymus weight to BW ratio of FRS birds were significantly higher than those of CRS birds. This was consistent with the findings of a previous study, which found that the thymus was the only lymphoid organ showing a significant difference among different free‐range days (Tong et al., ), indicating that birds had gradually adapted to the environment as the number of free‐range days increased.…”
Section: Discussionsupporting
confidence: 92%
“…Our observations revealed that thymus weight and the thymus weight to BW ratio of FRS birds were significantly higher than those of CRS birds. This was consistent with the findings of a previous study, which found that the thymus was the only lymphoid organ showing a significant difference among different free‐range days (Tong et al., ), indicating that birds had gradually adapted to the environment as the number of free‐range days increased.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, the spleen index was also improved by PGZ supplementation, especially in the 7.5 mg kg −1 PGZ group. These data suggest that the immune capacity of chickens was elevated …”
Section: Discussionmentioning
confidence: 82%
“…A possible reason is that as free-range chickens get more exercise, they will have a lower BW at slaughter and a higher FCR, which is confirmed by several studies (e.g., Castellini et al, 2002;Wang et al, 2009). However, others found no differences (e.g., Fanatico et al, 2005b;Tong et al, 2014) or even better productive performance in the free-range groups (e.g., Ponte et al, 2008a;Ponte et al, 2008b).…”
Section: Introductionmentioning
confidence: 97%